2010
DOI: 10.1016/j.jaci.2010.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of shared genetic factors between asthma and obesity in children

Abstract: Background Epidemiological studies consistently show associations between asthma and obesity. Shared genetics may account for this association. Objective To identify genetic variants associated with both asthma and obesity. Methods Based on a literature search, we identified genes from: 1) Genome-wide association studies (GWAS) of Body Mass Index (BMI) (n=17 genes), 2) GWAS of asthma (n=14) and 3) candidate gene studies of BMI and asthma (n=7). We used GWAS data from the Childhood Asthma Management Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 42 publications
1
102
1
Order By: Relevance
“…of hematopoiesis and tumorigenesis. Recently, a study showed that rs9494145 in MYB was associated with both asthma and BMI, although associations with BMI were modest and not signifi cant after correction for multiple comparisons ( 27 ). Further, the rs2952724/rs2629715 upstream of the SLIT2 gene, which is known to suppress tumor growth, had a lower frequency in nonresponders compared with responders.…”
Section: Fingen Replication Cohortmentioning
confidence: 99%
“…of hematopoiesis and tumorigenesis. Recently, a study showed that rs9494145 in MYB was associated with both asthma and BMI, although associations with BMI were modest and not signifi cant after correction for multiple comparisons ( 27 ). Further, the rs2952724/rs2629715 upstream of the SLIT2 gene, which is known to suppress tumor growth, had a lower frequency in nonresponders compared with responders.…”
Section: Fingen Replication Cohortmentioning
confidence: 99%
“…One of them included children from the Childhood Asthma Management Program 66 survey, Melén et al study. 67 The authors presumed that shared genetic factors are possibly associated with genes with pleiotropic effects, such as ADRB2, VDR, LEP, PRKCA, and TNFa. However, while genetic analysis did not reveal any association for these genes, together with no association for ADRB2, and with the comorbidity of asthma and obesity, a trend was observed for glucosamine-6-phosphate deaminase-2 (GNPDA2), protein tyrosine phosphatise, receptor type D (PTPRD), and roundabout axon guidance receptor homolog 1 (ROBO1), although further research is likely required.…”
Section: Shared Genetic Factors For Asthma and Obesitymentioning
confidence: 99%
“…Twin studies suggest that shared genetic pathways for asthma and obesity may partly explain the observed associations (20). Candidate gene studies and, more recently, genome-wide association studies have identified a large number of genes associated with either of the two conditions, but these genes do not seem to have a substantial impact on both phenotypes simultaneously (21). Candidate genes which seemed to be important for the asthma risk in obese people or for the higher BMI in asthmatics encompass LEP, TNFA, and PRKCA, regions encoding the adipose tissue derived Notes: Regression models were adjusted for age, sex, study area and smoking status.…”
Section: Asthma In Obese Peoplementioning
confidence: 99%